The Factors Influencing the Choices for Adaptation by Dairy Farmers to Climate Change in Fiji - Igbal, Mohammed Rasheed; Iqbaal, Ubaadah Bin; Bibi, Fazleen Farhat; Magiri, Royford Bundi (Journal of Cultural Analysis and Social Change, 2025)
Climate change has greatly impacted Fiji’s ecosystem including animal (livestock) and crop production from past decades and still greatly affects their economy. These climatic events include flooding, rise in ambient temperature, rise in the sea level, droughts, tropical cyclones, and all others that bring large changes to the environmental system. These large changes adversely affect animal production and the economy in Fiji. Not only this, but dairy farmers are also severely affected by climatic conditions such as loss of income and livestock species that die out during cyclones and other aspects. Not only the terrestrial species but the marine organisms are also affected since climatic changes bring alterations to their feeding period and the mating time leading to a vast decrease in organisms’ health, quality, and population. Consequently, the Fijian government and other Pacific organizations have brought strategies like adaptation plans to implement in animal production sectors. These plans and methods will help farmers in stimulating their farming systems and adapting to climatic changes and hence, this will lead to increased productivity and economy. The aim and objective of this review are to define and elaborate the climatic change effects on livestock and marine production in Fiji and effective solutions adopted by Fiji and other Pacific governments to refrain from adverse climate conditions.